2016
DOI: 10.1002/aoc.3452
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene‐substituted 3,3′‐diindolylmethanes with improved anticancer activity

Abstract: A series of ferrocene-substituted derivatives (2a-g) of the known drug 3,3′-diindolylmethane (DIM) were prepared and tested for their in vitro antitumor activity. The derivatives 2a (featuring indole moiety), 2b (featuring 2-methylindole moiety) and 2f (featuring 5-nitroindole moiety) were growth-inhibiting in vitro at lower concentrations than DIM in various tumor cells including pancreas cancer (BcPC-3), three DIM-resistant cancer cell lines (518 A2, KB-V1/Vbl, HT-29), triple-negative breast cancer (MDA-MB-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Most recently, ferrocene‐related anticancer research is also focusing on ferrocene–chalcogeno‐triazole–sugar conjugates, membrane interactions of nitroarylferrocenes, PEGylated ferrocene radiosensitizers of cancer cells, tubulin‐binding ferrocene‐substituted 3,3′‐diindolylmethane, ferrocene‐modified phospholipids, ferrocene–iminosugar hybrids, ferrocene–N‐heterocyclic carbene–gold(I) complexes targeting antioxidant pathways, and dendrimer‐related strategies . In terms of drug delivery, an elegant approach was reported by Wang's group with pH‐responsive supramolecular vesicles based on water‐soluble pillar[6]arene and ferrocene derivatives …”
Section: Ferrocenes In Nanomedicinementioning
confidence: 99%
“…Most recently, ferrocene‐related anticancer research is also focusing on ferrocene–chalcogeno‐triazole–sugar conjugates, membrane interactions of nitroarylferrocenes, PEGylated ferrocene radiosensitizers of cancer cells, tubulin‐binding ferrocene‐substituted 3,3′‐diindolylmethane, ferrocene‐modified phospholipids, ferrocene–iminosugar hybrids, ferrocene–N‐heterocyclic carbene–gold(I) complexes targeting antioxidant pathways, and dendrimer‐related strategies . In terms of drug delivery, an elegant approach was reported by Wang's group with pH‐responsive supramolecular vesicles based on water‐soluble pillar[6]arene and ferrocene derivatives …”
Section: Ferrocenes In Nanomedicinementioning
confidence: 99%
“…Compounds containing ferrocene, a compound with a sandwich-like structure with two cyclopentadienyl rings bound to an iron (II) center, have been evaluated in TNBC cell lines. [136][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155] Ferrocene and its derivatives (such as ferroquine and ferrocifen) have attractive qualities such as reversible redox properties and have displayed anticancer, antibacterial, antifungal, and antiparasitic activity. [136] Zhang and co-workers have reviewed the anticancer properties displayed by ferrocene-containing hybrids.…”
Section: Iron (Ii) Compoundsmentioning
confidence: 99%
“…[76] Moreover, both the hybrids lines, while DIM (IC 50 > 100 μM) was devoid of activity. [77] The SAR indicated that the introduction of either electron-donating or electron-withdrawing group into the C-2 and/or C-5 position of indole moiety was detrimental to the activity. Titanocene T (39) induced a moderate to good reduction in tumor growth compared with the control group without causing apparent toxicity in the mice model.…”
Section: Bisindole Hybridsmentioning
confidence: 99%